2002
DOI: 10.1021/ef020139q
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Production of Biphenyls from Oxidized Sulfur Compounds Obtained by Oxidative Desulfurization of Light Oils

Abstract: Photochemical production and recovery process of biphenyls from the desulfurization products, obtained by oxidative desulfurization (ODS) of light oils, has been investigated. The S-oxidized dibenzothiophenes (DBT sulfones), when dissolved in 2-propanol, were converted successfully into the corresponding biphenyls by photoirradiation at wavelengths of λ > 280 nm using a highpressure mercury lamp, under conditions of nitrogen atmosphere and at room temperature. The present photochemical process was found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The latter sulfur compounds fraction was analyzed using FI-MS (JEOL JMS-AX505H) to determine the concentrations of individual sulfur-containing compounds in VGO , …”
Section: Methodsmentioning
confidence: 99%
“…The latter sulfur compounds fraction was analyzed using FI-MS (JEOL JMS-AX505H) to determine the concentrations of individual sulfur-containing compounds in VGO , …”
Section: Methodsmentioning
confidence: 99%
“…The photochemical behavior of DBTO and the corresponding sulfone DBTO 2 has been investigated extensively 34 . The seminal work of Jenks [35][36][37][38][39] , Greer 40,41 , Nakai 42 , Shiraishi 43,44 , and others 45 has provided important mechanistic insights and enabled the establishment of a general reaction framework that rationalizes the formation of various products observed during photochemical processes involving these compounds. In all cases, it has been established that irradiation of DBTO results in cleavage of the sulfoxide S-O bond to release sulfide DBT and atomic oxygen O( 3 P), which oxidizes the solvent.…”
Section: Mechanistic Investigations Of Thia-baeyer-villiger Oxidationmentioning
confidence: 99%
“…TBOT as a precursor. The CTM-41 composites with two different molar ratios of Si/Ti (5,50) were synthesized. The amount of 1.5 g of calcined MCM-41 was placed in a 100 mL round-bottom ask with 50 mL of dried hexane.…”
Section: Preparation Of the Catalystmentioning
confidence: 99%
“…Based on the literature, 48,49 the DBT (1) can be converted to DBT sulfone (2) in the presence of OHc and it is shown in Scheme 2. Shiraishi et al 50 reported that when DBT sulfone was dissolved in 2-propanol and photo irradiated at l > 280 nm by a high-pressure mercury lamp under air, the concentration of DBT sulfone decreases with time and the biphenyl concentration increased. In this work, as is shown in Scheme 2, rst DBT (1) can convert to DBT sulfone (2) in the presence of OHc and then DBT sulfone (2) is photoexcited by photo irradiation to form highly reactive 1,5-biradical (3) intermediate and then it is hydrogenated by OH groups of CTM-41 and further decomposed to form nally biphenyl (5).…”
Section: Possible Dbt Photocatalyzed Degradation Pathmentioning
confidence: 99%